Applied Study on Causes of Malaria and its Impact on the Health of Children in Sudan (International Journal of Financial, Administrative and Economic Sciences, 2024)
The problem of the research discusses in health field by attempting to seeking a causes of malaria and its impact on the health of children in Sudan. a–primary Data malaria test survey in White Nile state from Elduwaim town and Elsifaraia, Elmanara village, The main reason to select this area for the study according to  exposure  by epidemics diseases and suffering from  shortage of social and health services. By using questionnaire for mothers with babies admitted, with critical condition, Longitudinal Study design depending on cases. To collect data, we require to determine the sample size of population. A sample of 500 mothers of children are selected to present sample size required. The research objectives to measure the relationship between drinking water and malaria, measure the relationship between Cause of Malaria and environment, to measure the relationship between response and treatment-,to measure the relationship between Cause of malaria and Meals before and during illness,. By using the Statistical Package for Social Science (SPSS) Program version N. (21) The data analysis include simple descriptive statistics and applied statistics test with use cross tabulation, and other statistics measures. The results indicate there many problems for cause malaria even the respondents emphasis the Environmental more Factor to causes the child malaria or nutrition needed. The result slowed that the common complications are infection and all respondents suffer from infection by malaria and the 25% is infection more than two time and 24% more than three time and 20% is once time and the result indicate that the majority child illness related to the weight of child and bleeding disorder, convulsion malaria, noun immunization, not vaccination.